TAUHID DAN MORAL SEBAGAI KARAKTER UTAMA DALAM PENDIDIKAN ISLAM - Taufik Mukmin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
Moral character education and the unity necessarily require an exemplary figure as a role model to uphold good values ​​or rules. Here, the role of educators, especially teachers, parents, the community and the government as an exemplary figure so that learners are able to do imitation of moral behavior. Therefore, all parties are required to be actively involved, hence the need for synergy among the elements that so moral character education and the unity can continue to be sustainable.